2009
DOI: 10.1371/journal.pone.0006722
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Differentiation and Enrichment of Spinal Motor Neurons Derived from Human and Monkey Embryonic Stem Cells

Abstract: BackgroundThere are no cures or efficacious treatments for severe motor neuron diseases. It is extremely difficult to obtain naïve spinal motor neurons (sMNs) from human tissues for research due to both technical and ethical reasons. Human embryonic stem cells (hESCs) are alternative sources. Several methods for MN differentiation have been reported. However, efficient production of naïve sMNs and culture cost were not taken into consideration in most of the methods.Methods/Principal FindingsWe aimed to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 53 publications
4
76
0
Order By: Relevance
“…Transplanted ES cells will form teratomas, and thus, ES cells must be predifferentiated prior to grafting. Protocols have been developed to differentiate ES cells into neural precursors (27)(28)(29)(30) and specific neuronal (30)(31)(32) and glial lineages (33,34). Predifferentiated mouse ES cells transplanted into the injured rat spinal cord differentiated into neurons and glia and showed partial functional recovery (35).…”
Section: Es Cellsmentioning
confidence: 99%
“…Transplanted ES cells will form teratomas, and thus, ES cells must be predifferentiated prior to grafting. Protocols have been developed to differentiate ES cells into neural precursors (27)(28)(29)(30) and specific neuronal (30)(31)(32) and glial lineages (33,34). Predifferentiated mouse ES cells transplanted into the injured rat spinal cord differentiated into neurons and glia and showed partial functional recovery (35).…”
Section: Es Cellsmentioning
confidence: 99%
“…WNT, TGFb, and FGF/ERK Mature neurons (Sasaki et al, 2010) Cobalt chloride HIF-1a stabilization Cardiomyocyte differentiation to functionally mature cardiomyocytes (Ng et al, 2011) Corticosteroids Trophoblast and mesodermal (Barbaric et al, 2010) CSA Calcineurin NFAT Cardiomyocyte differentiation from ESC-derived mesodermal cells in visceral endodermal stromal cell co-culture (Mummery et al, 2003) Decreased hypertrophy of ESC-derived cardiomyocytes (Lim et al, 2000) Cyclopamine SMO Hh Astrocytes Cymarin RARs/RXRs Mesodermal/endodermal (Desbordes et al, 2008) Dorsomorphin ALK2, 3 and 6 TGFb Neurogenesis Wada et al, 2009;Zhou et al, 2010) …”
Section: Downregulation Of Sulfonationmentioning
confidence: 99%
“…Of further interest was their finding that dorsomorphin was ineffective at inducing neural conversion in mESCs, demonstrating that small molecules may have species-specific effects . Additionally, it was demonstrated that dorsomorphin is important in the initial differentiation of NSCs/NPCs for the induction of spinal motor neuron differentiation from hESCs (Wada et al, 2009).…”
Section: Tgf-b Pathway-mediated Hesc Differentiationmentioning
confidence: 99%
“…Because neuroectodermal cells differentiated from hESCs generally have a rostral character, motoneuron differentiation is then achieved by the caudalizing factor retinoic acid followed by the ventralizing factor Shh (Li et al, 2005). Small molecules that can activate the Shh signaling, purmorphamine and SAG (a chlorobenzothiophene-containing Hh pathway agonist), have been shown to be effective as substitutes of Shh in motoneuron differentiation , Wada et al, 2009). The use of Hb9 (homeobox gene selectively expressed in motoneurons) promoter driven GFP hESCs allows isolation of a fairly pure population of motoneurons (Singh Roy et al, 2005).…”
Section: Neuronal Differentiation Of Human Escsmentioning
confidence: 99%
“…The use of Hb9 (homeobox gene selectively expressed in motoneurons) promoter driven GFP hESCs allows isolation of a fairly pure population of motoneurons (Singh Roy et al, 2005). Enrichment of derived motoneurons, up to 80%, was also shown to be achieved by gradient centrifugation in Biocoll (Wada et al, 2009) …”
Section: Neuronal Differentiation Of Human Escsmentioning
confidence: 99%